Struggle for Peace: Complementary Models in the Context of India - Pushparajan, A (Journal of Dharma, 1986)
Peace experience as a source of blessedness and a fountain of happiness is deeply embeaded in all the great religious literature, both philosophic and devotional. The hymns of Vedas are replete with the tripple benediction: "0m, Shanti, Shanti, Shanti". The religious philosophies of Stoicism and Platonism were evidently efforts to go to the source of an "imperturbable peace". Likewise Confucianism was also permeated with the ideals of "calm". Not much different were goals set by Taoism and Buddhism. Needless to refer to the Semetic religions. Not only d ’d Judaism introduce the word Shalom (peace) as a word of greetings, but also the prophets look forward to establishment of perfect peace in society, with the coming of the Messiah, "the prince of Peace". The very birth of Jesus Christ was hailed by Angels as an event of giving peace to men of good-will. And he himself blessed the peace-makers as children of God. Again, the recurring theme of all his apparitions after Resurrection was imparting of peace only. As regards Islam its very name indicates peace. Salam is itself a version of Shalom. In fact, it was so named because it was supposed to bring about the peace-experience among the various religions, races, colours and. communities.